Manipulating light : reflection, refraction, and absorption - Stille, Darlene R. (Minneapolis, MN : Compass Point Books, 2006)
Presents a simple study on the physics of light and how light waves behave, and examines why stars twinkle, how telescopes and prisms work, and more.
How light behaves -- Laws of reflection -- Mirrors: reflected light rays -- Refraction -- Absorption.
Includes bibliographical references (p. 47) and index.
School Library Journal
Science Books & Films (A.A.A.S.)
5.9
5-8
5-8
Keywords: Light absorption -- Juvenile literature; Light -- Juvenile literature; Reflection (Optics) -- Juvenile literature; Refraction -- Juvenile literature; Light absorption; Light; Reflection (Optics); Refraction; Light absorption; Light; Reflection (Optics); Refraction